2008
DOI: 10.1016/j.jcmg.2007.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Glucose Regulation Is Associated With Lipid-Rich Coronary Plaque

Abstract: Coronary lesions in patients with AGR are associated with more lipid-rich plaque content, which may be related to the increased IR in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(55 citation statements)
references
References 27 publications
2
49
1
Order By: Relevance
“…32 Amano et al also reported that coronary lesions in patients with impaired glucose metabolism are associated with greater lipid-rich plaque content. 33 The present finding of an association between high MAGE and TCFA at the non-culprit plaque in patients with mild-moderate stenosis, is consistent with the aforementioned studies. In addition, GV has a more specific triggering effect on oxidative stress than sustained hyperglycemia.…”
Section: Grant Supportsupporting
confidence: 92%
“…32 Amano et al also reported that coronary lesions in patients with impaired glucose metabolism are associated with greater lipid-rich plaque content. 33 The present finding of an association between high MAGE and TCFA at the non-culprit plaque in patients with mild-moderate stenosis, is consistent with the aforementioned studies. In addition, GV has a more specific triggering effect on oxidative stress than sustained hyperglycemia.…”
Section: Grant Supportsupporting
confidence: 92%
“…Lipid-rich plaques (LRP) were defined as increased lipid volume (> median) and greater lipid content (%LV >49% and %FV <50%), which occurred in the 75 th percentile of %LV and 25 th percentile of %FV in the present study population. 11, 12 The Bland -Altman test was applied to assess concordance of measurements. Multivariate Cox proportional hazards analysis was applied to study the predictors of clinical events adjusting for confounding factors (age, sex and body mass index) and predefined variables.…”
Section: Discussionmentioning
confidence: 99%
“…11, 12 In conventional IVUS, cross-sectional images were quantified for lumen cross-sectional area (LCSA), external elastic membrane (EEM), cross-sectional area (CSA), and plaque (P) + media (M) cross-sectional area (P + M CSA = EEM CSA -LCSA) using software built into the IVUS system. An eccentricity index of P + M was calculated with the formula of (maximum P + M thickness -minimum P + M thickness)/maximum P + M thickness.…”
Section: Conventional and Ib-ivus Parametersmentioning
confidence: 99%
“…Amano et al reported that coronary lesions in patients with abnormal glucose metabolism are associated with lipid-rich plaque components on integrated backscatter-IVUS. 19 Furthermore, metabolic syndrome is also associated with lipid-rich plaques. 20 These lipid-rich plaques are associated with the prevalence of acute coronary syndrome.…”
Section: Discussionmentioning
confidence: 99%